An ecoregion-specific ammonia emissions inventory of Ontario dairy farming: Mitigation potential of diet and manure management practices. (February 2016) - Chai, Lilong; Kröbel, Roland; MacDonald, Douglas; Bittman, Shabtai; Beauchemin, Karen A.; Janzen, H. Henry; McGinn, Sean M.; Vanderzaag, Andrew
Abstract: The Canadian ammonia (NH3 ) emissions model and a survey of dairy farm practices were used to quantify effects of management on emissions from dairy farms in Ontario Canada. Total NH3 emissions from dairy farming were 21 Gg NH3 –N yr −1 for the four ecoregions of the province. Annual emission rates ranged from 12.8 (for calves in ecoregions of Manitoulin-Lake Simcoe-Frontenac) to 50 kg NH3 –N animal −1 yr −1 (for lactating cows in ecoregions of St. Lawrence Lowlands) (mean of 27 kg NH3 –N animal −1 yr −1 ). The St. Lawrence Lowlands ecoregion had the highest emission rate because more dairy manure was managed as solid manure in that ecoregion. Total dairy cattle N intake (diet-N) was 81 Gg N yr −1, 23% of which was retained in animal products (e.g., milk, meat, and fetus), 47% was returned to the land, and 30% was emitted as gas (i.e., NH3 –N, N2 O–N, NO–N, and N2 –N) and nitrate-N leaching/runoff. Ammonia volatilization constituted the largest loss of diet-N (26%), as well as manure-N (34%). Reducing the fraction of solid manure by 50% has the potential to mitigate NH3 emissions by 18% in Ontario ecoregions. Highlights: The Canadian-specific NH3 emission model was revised and improved for dairy farming. NH3 emissions inventory of Ontario dairy cattle was quantified. Manure land application has greater emission potential than other stages in Ontario. Effects of mitigating practices on NH3 emissions were evaluated with the model.